Analysis on Lean Management of Real Estate Projects Oriented by Target Cost Management - Ma, Chao (Transactions on Economics, Business and Management Research, 2024)
At present, the state has more and more regulatory policies for the real estate industry, and the regulatory intensity is also greater. With the introduction of national policies and the impact of the downturn in the real estate market, industry competition has become increasingly fierce. Under this situation, if real estate companies want to avoid being eliminated by the market, they must rely on their own efficiency levels and management capabilities. Therefore, strengthening cost control on projects is an inevitable choice and important means for real estate companies. In recent years, with the slowdown of economic growth and the state’s regulation of the real estate industry, the sustainable development of the real estate industry has faced increasing challenges. This article is oriented by target cost management and focuses on the lean process of real estate development projects. The key points of management and its management strategies are discussed to provide industry reference.